Inhibitory effect of terfenadine on Kir2.1 and Kir2.3 channels - Delgado-Ramírez Mayra; Rodriguez-Leal Fanny Junue; Rodríguez-Menchaca Aldo Azmar; Moreno-Galindo Eloy Gerardo; Sanchez-Chapula José Antonio; Ferrer Tania (Acta Pharmaceutica)
Terfenadine is a second-generation H1-antihistamine that despite potentially can produce severe side effects it has recently gained attention due to its anticancer properties. Lately, the subfamily 2 of inward rectifier potassium channels (Kir2) has been implicated in the progression of some tumoral processes. Hence, we characterized the effects of terfenadine on Kir2.x channels expressed in HEK-293 cells. Terfenadine inhibited Kir2.3 channels with a strikingly greater potency (IC50 = 1.06 ± 0.11 μmol L−1) compared to Kir2.1 channels (IC50 = 27.8 ± 4.8 μmol L−1). The Kir2.3(I213L) mutant, possessing a larger affinity for phosphatidylinositol 4,5-bisphosphate (PIP2) than the wild-type Kir2.3, was less sensitive to terfenadine inhibition (IC50 = 13.0 ± 2.9 μmol L−1). Additionally, the PIP2 intracellular application had largely reduced the inhibition of Kir2.1 channels by terfenadine. Our data support that Kir2.x channels are targets of terfena-dine by affecting their interaction with PIP2, which could be regarded as a mechanism of the antitumor properties of terfenadine.